Single bulb garlic oil improves interleukin-6 via decreased reactive oxygen species (ROS) in high-fat diet male mice - Ilmawati, Riza Rahayu; Gofur, Abdul; Lestari, Sri Rahayu (Faculty of Medicine, Trisakti University, 2019)
BackgroundHigh-fat diet (HFD) is highly responsible for the development of excessive reactive oxygen species (ROS). ROS and low-density lipoprotein (LDL) then trigger macrophage activation to secrete interleukin-6 (IL-6). Single bulb garlic or in Indonesian called bawang lanang is traditional medicine that possesses strong antioxidant properties. This study aimed to evaluate the effect of single bulb garlic oil (SBGO) on ROS, IL-6, and lymphocyte density in HFD-fed male mice.MethodsThis was an experimental study on 24 male mice randomly subdivided into 6 groups: one group was fed a normal diet, whereas the remaining five groups were fed HFD for 45 days and were then treated with single bulb garlic oil 0 mg/kg, simvastatin 26 mg/kg BW, single bulb garlic oil 12.5 mg/kg BW, 25 mg/kg BW, and 50 mg/kg BW respectively for the next 35 days. At the end of treatment, the mice were dissected for collection of (i) serum in order to measure ROS and IL-6 levels using ELISA, (ii) aortas to measure IL-6 expression using immunohistochemistry-fluorescence (IHC-F) and to obtain lymphocytes from bone marrow and spleen which were then counted using a light microscope.ResultsOur results indicated that SBGO decreased the ROS level, IL-6 level, IL-6 expression, and lymphocyte density in HFD mice. SBGO 12.5 mg/kg BW is the optimum dose in our study to reduce inflammation in HFD male mice.ConclusionSBGO is useful to reduce inflammation and improve antioxidant imbalance, thus might be a potential antiatherogenic agent.